2017
DOI: 10.5937/ffr1702091h
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative activity of chitosan and chitosan based biopolymer film

Abstract: ABSTRACT:Growing consumer demand for the food without chemical preservatives focused significant extent of research in the direction of finding natural compounds that can be used in food preservation. In this context, natural substances with strong antimicrobial and antioxidant properties, like essential oils, as well as natural biopolymers, particularly draw attention. Natural biopolymers can serve as carriers of the active components, such as essential oils in order of their sustained release to the food dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Statins, chitosan and other products controlling cholesterol and lipids together with an adequate change in lifestyle and an appropriate diet are generally used to lower lipids with the final target effect of controlling the progression of atherosclerosis characterized by the growth of IMT, the genesis of plaques and possible cardiovascular events [18][19][20]. Pharma-Standard supplements of natural origin are ideal for long-term management in asymptomatic subjects as they do not expose preclinical subjects to side effects (as observed in some 30% of subjects regularly using statins).…”
Section: Discussionmentioning
confidence: 99%
“…Statins, chitosan and other products controlling cholesterol and lipids together with an adequate change in lifestyle and an appropriate diet are generally used to lower lipids with the final target effect of controlling the progression of atherosclerosis characterized by the growth of IMT, the genesis of plaques and possible cardiovascular events [18][19][20]. Pharma-Standard supplements of natural origin are ideal for long-term management in asymptomatic subjects as they do not expose preclinical subjects to side effects (as observed in some 30% of subjects regularly using statins).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Park et al demonstrated that with the increase in deacetylation degree, the antioxidant activity of CS would increase [16]. Hromis et al observed that the antioxidant activity of CS with 98% degree of deacetylation was 78.5%, while that of CS with 90% degree of deacetylation was only 51.5% [17].…”
Section: Introductionmentioning
confidence: 99%
“…Natural biopolymers can serve as transporters for a variety of active ingredients, such as essential oils, to ensure their prolonged release to the food items throughout storage. They may also show potential for safeguarding food goods from oxidation and microbiological spoilage (Hromiš et al, 2017).…”
Section: Introductionmentioning
confidence: 99%